2018
DOI: 10.1176/appi.ps.201700353
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Positive and Negative Responses to Reading Mental Health Clinical Notes Online

Abstract: Patients receiving mental health care frequently reported benefits from reading OpenNotes, yet some experienced negative responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 11 publications
(19 reference statements)
1
47
0
4
Order By: Relevance
“…Notably, a diagnosis of a psychotic, bipolar, or a personality disorder demonstrated no significant association with a negative emotional response to OpenNotes. 55,59 In March 2014, Beth Israel Deaconess Medical Center in Boston, United States, also began sharing behavioral health notes with 360 patients, publishing the organization's belief that doing so could benefit those with a spectrum of disorders as well as meaningfully influence the way clinicians frame their own thinking about their patients. 60 Since then, almost 60 organizations throughout the United States and Canada have started sharing behavioral health notes with patients.…”
Section: Clinicians' Perspectives On Opennotesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a diagnosis of a psychotic, bipolar, or a personality disorder demonstrated no significant association with a negative emotional response to OpenNotes. 55,59 In March 2014, Beth Israel Deaconess Medical Center in Boston, United States, also began sharing behavioral health notes with 360 patients, publishing the organization's belief that doing so could benefit those with a spectrum of disorders as well as meaningfully influence the way clinicians frame their own thinking about their patients. 60 Since then, almost 60 organizations throughout the United States and Canada have started sharing behavioral health notes with patients.…”
Section: Clinicians' Perspectives On Opennotesmentioning
confidence: 99%
“…[49][50][51]55 • Pay close attention to potential reactions of stress or anxiety in response to note content, particularly in patients with PTSD. 59 • Where appropriate, use note content as a means of psychoeducation, explaining technical verbiage or content in lay terms. • Avoid labels that may be perceived as judgmental and instead use language that highlights the patient's individuality and strengths.…”
Section: Recommendations For Research and Practicementioning
confidence: 99%
“…This movement is supported by our and others' prior research with patients receiving mental health care, which has shown that reading progress notes often helps patients feel more in control of their health care, better able to understand their mental health and general medical conditions, and better able to remember their plan of care and to have more trust in clinicians. In contrast, relatively few patients have reported frequently feeling distress or worry after reading their notes (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Patients reported that the medical notes eased their uncertainty, relieved anxiety, and facilitated control [74]. Denneson et al [75] found that reading OpenNotes helped 49% of patients have feelings ranging from very to extremely in control of their health care. Another study observed that access to notes increased patient trust toward their health care providers [92].…”
Section: Medical Notesmentioning
confidence: 99%
“…For subsets of patients, access to medical notes increased their anxiety levels [74]. One study found that 26% of the patents experienced stress or worry sometimes, whereas 8% reported often or always [75]. The study also reported that 18% of patients felt upset sometimes after reading their notes, compared with 8% who reported often or always.…”
Section: Medical Notesmentioning
confidence: 99%